Green buildings in Malaysia towards greener environment: Challenges for policy makers - Suhaida M.S.; Tan K.L.; Leong Y.P. (Institute of Physics Publishing, 2023)
The launch of the National Green Technology Policy (NGTP) in 2009 is a manifesto of the government's seriousness in implementing green initiatives for the country. Specifically for buildings, the government promotes the application of renewable energy (RE) and energy efficiency (EE) and the application of green building index. With the introduction of Low Carbon Cities Framework, Green Pass, Green Neighbourhood, Green Building Index by various agencies and organisations in Malaysia, it is time to look back and see how all these tools could come together. This paper attempts to identify the challenges in harmonising the green initiatives for policy makers toward greener environment for sustainability. Published under licence by IOP Publishing Ltd.